Intimacy in young people through the use of social networks - Zuluaga Salazar, María Acened (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
This work of investigation was realized with the intention to include/understand how the young people of degree eleven of the High School Divino Salvador of The Star Country in 2011were assuming the privacy concept, from the use of the social network Facebook. For their elaboration several authors considered as referring theoreticians and an own hermeneutical methodology of social sciences were implemented, which seted out with the application of tools like the individual interview semistructured and the interview to focal group, that allowed to demonstrate and to include how these young people although they have not changed in its perception on the privacy concept, if they are giving a more open use him in the social networks. Although the young people continue considering the privacy more from the sexual thing, do not assume that he is dangerous to share personal information. Also, he managed himself to identify that now they give a great value to the confidence when recognizing that at present it is easier to speak to them with his parents and to trust certain intimate information to them.